Diagnosis and Treatment of Paracoccidioidomycosis in the Maxillofacial Region: A Report of 5 Cases - Antonio Dionízio De Albuquerque Neto; André Vitor Alves Araújo; Daniel Assunção Cerqueira; Lorenzzo De Angeli Cesconetto; Nilton Provenzano; Eder Magno Ferreira de Oliveira (Case Reports in Otolaryngology)
Paracoccidioidomycosis is a fungal infection initially described in Brazil in 1908 by Adolfo Lutz. Manifestation of this disease depends on numerous factors, such as microorganism virulence, hormonal profile, genetic predisposition, nutrition, and immune system. It is characterized classically by cutaneous lesions, lymphadenopathy, and pulmonary involvement. It presents male predilection, which can be explained by the protective effect of female hormones. Classic presentation within oral cavity is a superficial ulcer characterized by hemorrhagic dots of moriform aspect. Treatment should be established individually and closely monitored. This manuscript aims at reporting five cases of this pathology.